P.F. Alexander (ed), Alan Paton Selected Letters: Author, Poet, Teacher, Christian Thinker, Activist and Penal Reformer – A Full, but not Uncontroversial Life (Historia, 2021)
This is a most useful and well-presented volume. As Phillips points out in his "Foreword", Paton (1903-1988) was not only the distinguished author of Cry the Beloved Country, but a school teacher, Christian thinker, organiser, political activist and penal reformer (p vii). This volume contains 350 letters of the 2 500 which survive. Paton was born in Pietermaritzburg and as a student at Natal University College, he began to write poetry. He also was President of the Student Representative Council. He became a teacher at Ixopo, married in 1928 and, after a serious illness in 1934, became a warden at an African reformatory in Diepkloof in what was then the Transvaal. Diepkloof had been an adult prison before being turned into a borstal for African youths. Paton worked to transform it into a school and the number of absconders fell dramatically. He felt passionately that his successes here could be applied to the country as a whole.